Refugiados e “Refugiados Ambientais” - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
With the intend of a better understanding about refugees, this article presents the definition of the term and the importance of the Convention relating to the Status of Refugees of 1951 and Protocol of 1967, they are essentials keys in the refugees protection. Being adressed the lack of recognition in International Law in relation to “environmental refugees”, that are not seen as a category of refugees, in any convention or international protocol. Showing cooperation as essential in the process of helping “environmental refugees” and the role of International Regimes and also showing the UNHCR as essential organ
Keywords: Refugiados; Ambientalistas; Cooperação internacional; Reconhecimento internacional; Degradação ambiental; CNPQ::CIENCIAS HUMANAS::CIENCIA POLITICA